REKONSTRUKSI FILSAFAT PENDIDIKAN ISLAMSEBAGAI PARADIGMA PENGEMBANGAN PENDIDIKAN KONTEMPORER - Romiyati; Arif Setiawan Alfiyanto; Naufal Hilmi; Zainuddin Abas; Siti Mahmudah Noorhayati (LPPM STAI Muhammadiyah Probolinggo, 2026)
Contemporary education faces various fundamental problems, such as the dichotomy between religious science and general science, pragmatic-economic orientation, and the weakening of the dimension of values and character. This problem shows that there is a philosophical crisis in the modern education paradigm that tends to be secular and positivistic. This article aims to reconstruct the philosophy of Islamic education as an alternative paradigm that is relevant in responding to contemporary educational challenges. This research uses a qualitative approach with a literature study method on classical and contemporary works in the field of Islamic philosophy of education as well as relevant scientific journal articles. The data were analyzed through the stages of reduction, conceptual categorization, and philosophical-contextual synthesis. The results of the study show that the philosophy of Islamic education has an integrative conceptual framework based on monotheism as an educational worldview, the principle of tawāzun (balance), the integration of knowledge and revelation, spiritual realism in the educational process, as well as the strengthening of Islamic values, social ethics, and humanism. This reconstruction is not only normative, but also has practical relevance in the development of a holistic and value-oriented Islamic education system and management. This article contributes theoretically to the development of the paradigm of Islamic education philosophy and provides strategic implications for the development of Islamic education policies and practices in the modern era.Keywords: Philosophy of Islamic education, paradigm reconstruction, contemporary education, monotheism, integration of knowledge